Cardiac sarcoidosis, the complete atrioventricular block of which was completely recovered by intravenous steroid pulse therapy - Watanabe, Hiroaki (J Cardiol Cases, 2015)
Atrioventricular block (AVB) in individuals with cardiac sarcoidosis (CS) is one of the major complications caused by inflammation of the conducting system of the heart, as a sign of worse prognosis. We report the case of a 53-year-old Japanese woman whose electrocardiogram showed complete AVB by the clinical diagnosis of CS. We administered intravenous methylpredonisolone (1 g/day) for 3 days. On the second day of steroid pulse therapy, the complete AVB improved to sinus rhythm of 1st degree AVB and complete right bundle branch block. Normal sinus rhythm was then observed after oral steroid therapy. These results suggest that in cases of complete AVB, steroid pulse therapy with a strong anti-inflammatory effect may be recommended first. <Learning objective: This case illustrates a typical case of CS with complete AVB, but the cardiac contraction was normal. In this setting, steroid pulse therapy may be effective when (1) the active inflammation of the conduction system can be suppressed by steroid pulse therapy; (2) the time to start steroid therapy is short enough to recover.>